2023
DOI: 10.1007/s11356-023-25527-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Self-reported After Events Following Immunization of COVID-19 Vaccines in Turkey and Bangladesh

Abstract: Though mass vaccination programs helped to reduce the severity of the ongoing pandemic, various unwanted effects were reported in Turkey and Bangladesh after taking vaccines. The purpose of this study was to evaluate and compare the adverse effects of several vaccines in Turkey and Bangladesh and how the population of both countries prioritizes the continuation of vaccination compared to the side effects. An online survey with a pretest was conducted to gather data over the research period from July 10, 2021 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…However, after the second dose, the percentage of AEs for Pfizer declined to 71.19%, whereas for Moderna, it was 86.09%. It is worth noting that while Pfizer and Moderna vaccines exhibited varying trends in AEs after the second dose, other vaccines such as Sinopharm, Sinovac, and Oxford-AstraZeneca demonstrated a significant reduction in AEs after the second dose during overall immunization [22]. For the AstraZeneca vaccine, this unusual trend of lower AEs after the second dose was also reported in two separate studies from the Kingdom of Saudi Arabia and the United Kingdom with large sample sizes [23,24].…”
Section: Discussionsupporting
confidence: 53%
“…However, after the second dose, the percentage of AEs for Pfizer declined to 71.19%, whereas for Moderna, it was 86.09%. It is worth noting that while Pfizer and Moderna vaccines exhibited varying trends in AEs after the second dose, other vaccines such as Sinopharm, Sinovac, and Oxford-AstraZeneca demonstrated a significant reduction in AEs after the second dose during overall immunization [22]. For the AstraZeneca vaccine, this unusual trend of lower AEs after the second dose was also reported in two separate studies from the Kingdom of Saudi Arabia and the United Kingdom with large sample sizes [23,24].…”
Section: Discussionsupporting
confidence: 53%
“…The Michels et al analysis found a nearly four-fold increase in cardiovascular SAEs among subjects in the Pfizer trial who received the BNT162b2 injection compared to placebo, a fact never reported to the public at the time of the rollouts in December 2020 [54]. Notwithstanding these grave concerns, the Moderna product has shown even more frequent AEs when compared to its Pfizer counterpart [116][117][118][119][120]135]. Both mRNA products were linked with increased risks of ischemic stroke, brain hemorrhage, acute coronary syndrome, and other conditions known to reduce life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some authors have observed fewer AEs after the second dose [ 134 ], others have reported an increased incidence [ 116 ]. Sultana et al reported varying trends in AEs after the second dose for both mRNA products, albeit with a higher frequency of AEs following the second-dose administration of the Moderna vaccine [ 135 ].…”
Section: Reviewmentioning
confidence: 99%
“…Conversely, close-ended questions restrict the range of potential answers by offering predefined choices, potentially constraining the accuracy and depth of responses (Taherdoost, 2022). Combined method is also can be found in a similar study to obtain the participants opinion on post-vaccination experienced (Sultana et al, 2023).…”
Section: Discussionmentioning
confidence: 99%